Pengaruh Penggunaan Media Sosial Tiktok terhadap Pola Komunikasi Mahasiswa: Studi Kasus di Fakultas Dakwah dan Komunikasi UIN Sumatera Utara - Dalimunthe, Maulana Andinata; Siregar, Aqilah Anisah Parkha; Marsanda, Siti Annisa (AHKAM, 2024)
This research aims to test the validity and reliability of the questionnaire used to measure the influence of the use of social media TikTok on student communication patterns at the Faculty of Da'wah and Communication, UIN North Sumatra. The validity test results show that the questionnaire can be considered valid for measuring the variables studied, while the reliability test results show that the questionnaire can be considered reliable because the respondents' answers are consistent from time to time. Furthermore, this research shows that the use of TikTok has a significant influence on students' communication patterns, especially in terms of duration of use, communication skills, and ability to build connections. Most students spend 1-3 hours a day using TikTok, and feel that using TikTok has quite an impact on their communication skills and helps in building connections. Therefore, this research provides a deeper understanding of the impact of TikTok use on students' communication patterns.